2021
DOI: 10.7717/peerj.10920
|View full text |Cite
|
Sign up to set email alerts
|

miR-155-5p upregulation ameliorates myocardial insulin resistance via mTOR signaling in chronic alcohol drinking rats

Abstract: Background Chronic alcohol intake is associated with an increased risk of alcoholic cardiomyopathy, which may present with pathological changes such as myocardial insulin resistance, leading to ventricular dilation and cardiac dysfunction. Although a correlation between microRNA-155 (miR-155) and insulin signaling has been identified, the underlying mechanism has not been elucidated to date. The purpose of the study was to determine whether overexpression of miR-155-5p in vivo could ameliorate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Both autophagy and miRNAs are involved in synaptic remodeling, neuronal plasticity, proliferation, apoptosis, and inflammation. ,, We speculate that a miRNA-autophagy pathway could play a role in the occurrence of epilepsy. For example, miRNA-155 has been reported to induce autophagy via the mTOR pathway . Beclin 1 is mainly located in cytoplasm in both human and rat cells; thus, miRNA could be involved in the regulation of Beclin 1 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Both autophagy and miRNAs are involved in synaptic remodeling, neuronal plasticity, proliferation, apoptosis, and inflammation. ,, We speculate that a miRNA-autophagy pathway could play a role in the occurrence of epilepsy. For example, miRNA-155 has been reported to induce autophagy via the mTOR pathway . Beclin 1 is mainly located in cytoplasm in both human and rat cells; thus, miRNA could be involved in the regulation of Beclin 1 .…”
Section: Discussionsupporting
confidence: 84%
“…For example, miRNA-155 has been reported to induce autophagy via the mTOR pathway. 28 Beclin 1 is mainly located in cytoplasm in both human and rat cells; thus, miRNA could be involved in the regulation of Beclin 1. 29 Beclin1 is an evolutionarily conserved protein that is recognized as a positive regulatory factor in the biogenesis of autophagosomes.…”
Section: Verification Of Hippocampal Transduction By Intracerebrovent...mentioning
confidence: 99%
“…Changes in miR-155-5p were reported in several studies in both animal and human models related to diabetes mellitus and cardiovascular pathogeneses. A recent study has reported that miR-155-5p upregulation affects myocardial insulin resistance via mTOR signaling in chronic alcohol-drinking rats [ 48 ]. Additionally, miR-155 deletion in female mice increases adipogenic, insulin sensitivity, and energy uncoupling machinery, while limiting inflammation in white adipose tissue, which together could restrict high-fat diet-induced fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the expression of miR-155 is upregulated in the (31). Several studies show that the mTOR signaling pathway is involved in miR-155-mediated regulation (16,22). In addition, mTOR contributes to glaucoma development and is associated with RGC activity (13,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Given that miR-155 functions via mTOR signaling (22) and mTOR was involved in RGC damage and glaucoma development (8), we next determined the role of mTOR in the protective effect of acteoside/miR-155 on RGC-5 cells. It was found that mTOR expression was decreased in H 2 O 2treated RGC-5 cells (Figure 6A), and miR-155 inhibition could induce mTOR expression (Figure 6B).…”
Section: Acteoside Protects Rgc-5 Cells Against H 2 O 2 -Induced Cell Injury Via the Mir-155/mtor Axismentioning
confidence: 99%